Prisoners in paradise : American women in the wartime South Pacific - Kaminski, Theresa, 1958- (University Press of Kansas, 2000)
The author presents stories of women who were imprisoned in the Philippines by the Japanese and of women who "fled into the hills or adopted new identities to avoid captivity, relying on neighbors and former servants for survival."--Jacket.